Physiotherapists’ perceptions on stroke rehabilitation with focus on palliative care in Lusaka, Zambia - Mwanza, Christo (University of the Western Cape, 2016)
Magister Scientiae (Physiotherapy) - MSc(Physio) === Palliative care is a vague and often confusing term used to describe a type of treatment model for chronic and life-threatening illnesses. WHO describes palliative care as an approach that improves the quality of life of patients and their families facing the problem associated with life-threatening illness by: early identification, impeccable assessment, and treatment of pain, physical, psychosocial and spiritual. The aim of this study is to explore the perceptions of physiotherapists on palliative care in order to contribute to the understanding of the role of physiotherapists to the care of stroke patient in Zambia. The objectives of this study are to explore physiotherapists’ knowledge on palliative care, their perceptions on management of palliative care as well as explore its application in the rehabilitation of stroke patients; and lastly to make recommendations on guidelines based on the outcomes of this study. Method: an exploratory study, using qualitative design was used. Data collection techniques were in-depth individual interviews and FGDs that consisted of purposively sampling of physiotherapists working; at four selected hospitals and a rehabilitation centre in Lusaka. Audio recording from the interviews was transcribed verbatim for each session by an independent person. The study employed thematic content analysis for data analysis. The data was classified systematically by means of coding to identify key factors or issues such as concepts, categories, themes and the relationship between them. Results indicated that all participants in the current study perceived palliative care as a medical care for the chronic and terminal ill patient in whom stroke patient and family will benefit if it is applied in the early stages of the disease trajectory; as well as it does improve the patient and family quality of life. Furthermore they emphasized on multidisciplinary team and holistic approaches in order to achieve all its tenets. Conclusion: the study had succeeded in exploring the physiotherapists’ perceptions on palliative care and contributed to the understanding of the role of physiotherapy to the care of stroke patients in general.